Creep of Frozen Sands - Sayles, Francis H (1968)
Unconfined compressive creep strengths and strains were measured for frozen saturated Ottawa sand (20-30) and Manchester fine sand. The creep tests were conducted at approximate stress levels of 60, 35, 20 and 5% of the conventional unconfined compressive strength. Testing temperatures were 15, 25, 29 and 31F. It was found that the unconfined compressive creep strength of the frozen sand can be predicted using two short-term, high-stress-level creep tests. (Author)